Exploring Theta Burst Stimulation for Post-traumatic Stress Disorder in Australian Veterans—A Pilot Study. Issue 9 (30th June 2020) - Nursey, Jane; Sbisa, Alyssa; Knight, Holly; Ralph, Naomi; Cowlishaw, Sean; Forbes, David; O'Donnell, Meaghan; Hinton, Mark; Cooper, John; Hopwood, Malcolm; McFarlane, Alexander; Herring, Sally; et al.
Abstract: Introduction: Post-traumatic stress disorder (PTSD) is a severe and debilitating condition affecting a significant proportion of the veteran community. A substantial number of veterans with PTSD fail to benefit from trauma-focused psychological therapies or pharmacotherapy or are left with residual symptoms, and therefore, investigation of new and innovative treatment is required. Theta Burst Stimulation (TBS) is a novel form of Repetitive Transcranial Magnetic Stimulation, which has been shown to improve depression symptoms and associated cognitive deficits. The current pilot study aimed to explore the acceptability, safety, and tolerability of intermittent TBS (iTBS) as a treatment for PTSD in Australian veterans. Materials and Methods: This study employed a case series, repeated-measures design. Eight Australian Defence Force veterans with PTSD received 20 bilateral iTBS treatments (1 session per day, 5 days per week over a 4-week period) and were assessed on a range of mental health and neuropsychological measures, including the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) and Hamilton Depression Rating Scale (HAM-D), at pretreatment, post-treatment, and a 3-month follow-up. Results: Treatment was generally welltolerated, with reported side-effects including mild to moderate site-specific cranial pain and headaches during stimulation, which were relieved with the use of low dose analgesics. No serious side effects or adverse events were reported. Participants exhibited reductions in both PTSD and depression symptom severity (the repeated-measures effect size [dRM ] for the CAPS-5 was −1.78, and the HAM-D was −1.16 post-treatment), as well as improvements in working memory and processing speed. Although significance cannot be inferred, these preliminary estimates of effect size indicate change over time. Conclusions: Bilateral iTBS appears to be welltolerated by Australian veterans. Within this repeated-measures case series, iTBS treatment shows promise in reducing both PTSD and mood symptoms, as well as improving cognitive difficulties associated with these disorders. Large-scale randomized controlled trials of this promising treatment are warranted.